PROSES INTERAKSI SOSIAL UNTUK MENINGKATKAN KARAKTER PERCAYA DIRI SISWA KELAS 1 SDN TANGERANG 19 - Annisa Natasya Putri; Ana Nurhasanah; Zerri Rahman Hakim (Jurnal Pendidikan Dasar, 2020)
The aim of this study is to describe how the process of social interaction to improve students’ confidence in learning process. The subject of this study are first grade students and the object is teacher at SDN 19 Tangerang. The object of this study is social interaction process to improve students' confidence. This study use descriptive qualitative as the method. The data collection is gathered through interview, observation and documentation. This study is use analysis technique, such as data reduction, data display, and conclusion drawer. The result of this study is that the social interaction of first grade students at SDN 19 Tangerang is already good. This condition leads to the improvement of students’ confidence in learning process, as the result they actively participate in learning process. Keyword : social interaction, confidence, learning process.